PENGARUH PENAMBAHAN TINTA CUMI-CUMI (Loligo sp) TERHADAP KUALITAS NUTRISI DAN PENERIMAAN SENSORIS MI BASAH - Agusandi Agusandi; Agus Supriadi; Shanti Dwita Lestari (Universitas Sriwijaya, 2013)
The purpose of this research was to determine the effect of addition squid ink to the quality of wet noodle. The completely randomized design was used in this research with 5 treatments and three replications. The treatment were 0%, 0,5%, 1%, 1,%% and 2% of squid ink. The parameter were chemical analysis (protein content, ash content, carbohydrate content, water content, and vitamin A), physical analysis (color and elongasi of wet noodle) and sensory test (color, aroma, texture and taste by hedonic test). The result show that the treatment was significant on color (lightness, chroma and hue), chemical analysis (protein content, carbohydrate content, and water content), hedonic (color and taste). Treatment of wet noodle A3 with combination squid ink 1,5 %, is the best treatment that liked by panel. The result of sensori evaluation with characteristic elongasi 72,67 %, lightness 35,050, hue 127,60, chroma 1,070, protein content 7,11 %, carbohydrate content 14,85 %, water content 52,57 %, and ash content 0,34 %.